Regional Hippocampal Atrophy and Higher Levels of Plasma Amyloid-Beta Are Associated With Subjective Memory Complaints in Nondemented Elderly Subjects - Cantero, Jose L; Iglesias, Juan E; Van Leemput, Koen; Atienza, Mercedes (The journals of gerontology. Series A, Biological sciences and medical sciences, 2016)
Evidence suggests a link between the presence of subjective memory complaints (SMC) and lower volume of the hippocampus, one of the first regions to show neuropathological lesions in Alzheimer's disease. However, it remains unknown whether this pattern of hippocampal atrophy is regionally specific and whether SMC are also paralleled by changes in peripheral levels of amyloid-beta (Aβ). The volume of hippocampal subregions and plasma Aβ levels were cross-sectionally compared between elderly individuals with (SMC(+); N = 47) and without SMC (SMC(-); N = 48). Significant volume differences in hippocampal subregions were further correlated with plasma Aβ levels and with objective memory performance. Individuals with SMC exhibited significantly higher Aβ1-42 concentrations and lower volumes of CA1, CA4, dentate gyrus, and molecular layer compared with SMC(-) participants. Regression analyses further showed significant associations between lower volume of the dentate gyrus and both poorer memory performance and higher plasma Aβ1-42 levels in SMC(+) participants. The presence of SMC, lower volumes of specific hippocampal regions, and higher plasma Aβ1-42 levels could be conditions associated with aging vulnerability. If such associations are confirmed in longitudinal studies, the combination may be markers recommending clinical follow-up in nondemented older adults.